Co-pyrolysis characteristic of biomass and bituminous coal. (March 2015) - Li, Shuaidan; Chen, Xueli; Liu, Aibin; Wang, Li; Yu, Guangsuo
Highlights: The co-pyrolysis characteristic of four different biomass and coal were studied. Weight fractions of the blended samples were compared with the calculation ones. Kinetic parameters of the blended samples were obtained. Abstract: Co-pyrolysis characteristics of biomass and bituminous coal have been studied in this work. The temperature was up to 900 °C with the heating rates of 10, 15, 20, 25 and 30 °C/min. Rice straw, saw dust, microcrystalline cellulose, lignin and Shenfu bituminous coal were chosen as samples. Six different biomass ratios were used. The individual thermal behavior of each sample was obtained. The experimental weight fractions of the blended samples and the calculated values were compared. The results show that the weight fractions of the blended samples behave differently with calculated ones during the co-pyrolysis process. With the increasing biomass ratio, relative deviations between experimental weight fractions and calculated ones are larger. H/C molar ratio, heat transfer properties of biomass would affect to the interaction between biomass and coal. The maximum degradation rates are slower than the calculated ones. The activation energy distributions also changed by adding some biomass into coal.